Dinosaur macroevolution and macroecology - Benson, R (Annual Reviews, 2018)
Dinosaurs were large-bodied land animals of the Mesozoic that gave rise to birds. They played a fundamental role in structuring Jurassic–Cretaceous ecosystems and had physiology, growth, and reproductive biology unlike those of extant animals. These features have has made them targets of theoretical macroecology. Dinosaurs achieved substantial structural diversity, and their fossil record documents the evolutionary assembly of the avian body plan. Phylogeny-based research has allowed new insights into dinosaur macroevolution, including the adaptive landscape of their body size evolution, patterns of species diversification, and the origins of birds and bird-like traits. Nevertheless, much remains unknown due to incompleteness of the fossil record at both local and global scales. This presents major challenges at the frontier of paleobiological research regarding tests of macroecological hypotheses and the effects of dinosaur biology, ecology, and life history on their macroevolution.